Research of Information Retrieval Data Processing in Commercial Electronic Resources - Budko, Daria; Sharonova, Nataliia (My University, 2021)
The article provides an overview of existing methods of processing textual data in order to improve the site's performance and quickly find information about the product that the user needs: substantiated the relevance of the research topic, analyze the classification of problems, search and processing of textual information.
Keywords: Information retrieval; methods of classification